Effects of Moxibustion on Central Fatigue in Rats Subjected to Different Degrees of Exhaustive Exercise - Liang, Yu-lei; Xu, Xiao-kang; Gao, Fei; Wu, Zhong-qiu; Zhu, Jie; Zhou, Xiao-hong; Zhang, Zhi-fang; Sun, Li-hong; Sun, Dong-yun (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2019)
Objective To observe the effects of moxibustion on central fatigue in rats subjected to different degrees of exhaustive exercise.Methods The exhaustive exercise model was established through repeated trials of swimming. Ninety-six male SD rats were randomly divided into the following three groups: a control group (n=32) that did not undergo the exercise routine, an untreated group (n=32) that received no treatment after exercise, and a moxibustion group (n=32) that received a mild dose of moxibustion at “Shénquè” (CV 8) for 15 min after exercise. Rats in each group were randomly and equally divided into 1st, 4th, 7th and 10th trial subgroups according to exercise duration. The levels of hippocampal tissue monoamine neurotransmitters 5-hydroxytryptamine (5-HT), Dopamine(DA) and free radicals Malondialdehyde (MDA), Superoxide dismutase (SOD), Glutathione peroxidase (GSH-Px) were measured after the exhaustive exercise protocol for each group.Results The exhaustive duration of rats in the 4th trial untreated subgroup was significantly longer than the 1st trial untreated subgroup, while the 7th and 10th trial untreated subgroups were significantly shorter than the 1st trial untreated subgroup. The 7th and 10th trial moxibustion subgroups were longer than the corresponding untreated subgroups. Compared with the control group, the levels of 5-HT and MDA in rat brains for each untreated subgroup were higher and the GSH-Px levels in the 4th, 7th and 10th trial untreated subgroups were lower. The levels of brain DA and SOD in rats from the 1st trial untreated subgroup were significantly higher than controls and then decreased. The 7th and 10th trial untreated subgroups were significantly lower. Compared with the corresponding untreated subgroups, the levels of rat brain 5-HT in the 7th and 10th trial moxibustion subgroups were decreased, the MDA levels in the 4th, 7th and 10th trial moxibustion subgroups were decreased, and the DA,SOD, GSH-Px levels in the 4th, 7th and 10th trial moxibustion subgroups were increased.Conclusions Moxibustion relieved exercise-induced central fatigue in long-term exercise by reducing the levels of 5-HT and MDA while increasing the levels of DA, SOD, and GSH-Px, effectively extending the duration of the exhaustive exercise.
Keywords: exhaustive exercise; moxibustion; hippocampal; neurotransmitter; free radical